Investigation of impregnated commercial rice husks activated carbon with alkanolamine as carbon dioxide (CO2) adsorbent - Siti Noraishah, Masoum Raman; Saidatul Shima, Jamari; Noor Asma Fazli, Abdul Samad; Nur Aminatulmimi, Ismail (Asian Research Publishing Network (ARPN), 2016)
The adsorption capacity of the activated carbon can be increased by introducing the amine group on the surface of the adsorbent. Modified rice husk activated carbon with different concentration and mixture ratio were prepared using wet impregnation method with alkanolamine. The adsorbents obtained were characterized by X-Ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR) and Field Emission Scanning Electron Microscopy (FESEM). From XRD analysis, the diffraction angles around 21.66° to 22.18° were linked for pyrazole, ethanolamine and diethanolamine which prove the presence of hydrocarbon and amine on the activated carbon surfaces. The presence of amide functional groups in FTIR analysis at 3288 cm-1 and 1651 cm-1 band proved that there was a reaction occured between carboxyl groups on the activated carbon surfaces with amine bond. For FESEM analysis, it was shown that the morphology of the non-modified activated carbon contains many pores on its surface while the pores on the modified activated carbon were covered with alkanolamines according to the selected concentrations.